Production of gamma-rays by inverse Compton scattering in jets. - Bednarek, W.; Kirk, J. G.; Mastichiadis, A. (1996)
We discuss a model for the γ-ray production in blazars in which electrons are accelerated rectilinearly in localised regions of the jet, scattering soft radiation from the accretion disk. In our model the jet divides naturally into two zones. In the `radiation dominated zone' (close to the disk), the acceleration of electrons is balanced by inverse Compton losses in the Thomson regime and energy is efficiently transferred into the γ-rays. The γ-ray spectral slope is determined by the electric field profile along the jet. In the `particle dominated zone' (further from the disk) the electron losses are too low to balance acceleration and the electrons are injected into the jet with energies corresponding to the full potential drop in the acceleration region. We suggest that these electrons are then isotropised by the random component of the magnetic field of the jet and cool mainly by synchrotron losses. In the framework of our model we predict further that Galactic black hole candidates might be sources of γ-radiation; in this case, however, we do not expect emission above 10GeV.
Keywords: acceleration of particles; GALAXIES; GALAXIES: INDIVIDUAL: MRK 421; gamma rays: theory; Jets; MRK 501